Nog nadenke na aanleiding van "Nadenke van "n Afrikaner" deur HJC Pieterse - Niekerk, A. S. van (1990)
Considering the reflections of HJC Pierterse on the Afrikaner In a recent publication the theologian HJC Pieterse reflected on the spiritual and existential condition of the modern Afrikaner, and his feelings of guilt, loneliness and hopelessness. In this article it is argued, by comparing Pieterse’s reflections to Afrikaans literature, that the Afrikaner has, since the beginning of the 20th century, been moving away from the soil and from his African contacts, and has become more and more European and American in his thinking. Apartheid was meant to finalise his separateness from Africa. The resistance of the modern Afrikaner to apartheid does not, however, bring a new relation to Africa. It is rather one further step closer to European thinking.
Keywords: Sociology and Ethics; Ancient Semitic and Classical Languages; Philosophy; Aspects of Religious Studies; Practical Theology; Ministers of Religion; Scholars; Philosophers; Theologians; Netherdutch Reformed Church; Theology